The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31729/jnma.3674
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Attitude and Knowledge of the Principles and Practices of Orthodontic Treatment Among the Non-orthodontic Specialists and General Practitioner Dentists

Abstract: Introduction: General practitioner dentists and non-orthodontic specialties ought to have the knowledge of the basic principles and practices of orthodontics in order to educate the patients, diagnose their problems correctly and for proper referral. The objective of the present study is to assess the attitude and knowledge of the general practitioner dentists and non-orthodontic specialists towards the basic principles and practices of orthodontics. Methods: This study was performed by presenting a clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…In contrast to the present study, study done by Kapoor et al have shown statistically significant knowledge and attitude difference between general dentists and nonorthodontic specialists. 8 Similarly, Sastri et al showed that the scores were more for the non-orthodontic specialists and the difference was statistically significant. 6 In another study done in Saudi Arabia, when the scores of knowledge were compared between general dental practitioner and non-orthodontic specialties, a statistically significant difference was noted.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast to the present study, study done by Kapoor et al have shown statistically significant knowledge and attitude difference between general dentists and nonorthodontic specialists. 8 Similarly, Sastri et al showed that the scores were more for the non-orthodontic specialists and the difference was statistically significant. 6 In another study done in Saudi Arabia, when the scores of knowledge were compared between general dental practitioner and non-orthodontic specialties, a statistically significant difference was noted.…”
Section: Discussionmentioning
confidence: 93%
“…In such case, it is essential for a dentist to identify and diagnose the orthodontic cause and advice for a referral. 8 Therefore, there is a need to identify the knowledge level of general dental practitioners and nonorthodontist specialists with respect to the orthodontic treatment. The objective of the study was to assess the knowledge of orthodontic treatment among general dentists and non-orthodontic specialists and to compare the knowledge of orthodontic treatment between the two groups.…”
mentioning
confidence: 99%
“…They should be aware of the common understanding of orthodontic problems and develop a habit of referral to an orthodontist. A study conducted to evaluate the basic knowledge and practices of GDPs and non-orthodontist practitioners revealed reduced knowledge and practices 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, no se sabe mucho sobre los verdaderos beneficios de la ortodoncia interceptiva en el nivel más alto de evidencia deseado y todavía existen algunos vacíos al respecto (2). La maloclusión tiene una variedad etiológica amplia pero los resultados son bastante comu-nes, incluida la apariencia poco estética, malestar del paciente, problemas periodontales, dificultad para masticar y problemas del habla, lo cual exige un enfoque multidisciplinario por parte de cirujanos dentistas y especialistas, basado en el conocimiento de los principios y prácticas de la ortodoncia (3) . Se estima que en un 65.1% de todos los casos ortodónticos son tratados por especialistas de ortodoncia, un 3.7% por odontopediatras y un 31% son tratados por odontólogos generales (4) .…”
Section: Introducción Y Antecedentesunclassified